STRATEGI SEKOLAH DALAM MEMBUDAYAKAN POLA HIDUP SEHAT KEPADA PARA SISWA DI SDIT AL-HIJRAH 2 DELI SERDANG - Dini, Alifah; Dora, Nuriza; Hati, Silvia Tabah (Islamijah: Journal of Islamic Social Sciences, 2024)
This research aims to analyze the strategies carried out by schools in cultivating healthy lifestyles among students at SDIT Al-Hijrah 2 Deli Serdang. Schools not only pay attention to strategies in implementing learning but also pay attention to student health which is done by cultivating the school so that students get used to healthy living behavior. This research uses qualitative research using analytical descriptive methods. Data was obtained using data collection techniques in the form of observation, interviews and documentation. The aim of this research is to determine the strategy, implementation and impact of the healthy living culture carried out at SDIT Al-Hijrah 2 Deli Serdang. The results of this research show that (1) the strategy carried out by schools in cultivating healthy lifestyles is carried out by habituation (enculturation) in the form of written rules outlined on banners in the school environment, conveying various important information to parents through FKOMG, habituation or acculturation (enculturation ) in each class, and through the P5 program. (2) Implementation of strategies for cultivating a healthy lifestyle is carried out in several ways, namely the unavailability of canteens, healthy eating patterns, provision of drinking water in schools, school catering, afternoon naps, maintaining environmental cleanliness, exercise, and fasting on Mondays and Thursdays. (3) The impact of the strategy and implementation of a healthy lifestyle makes students disciplined, self-controlled and independent, has a sense of responsibility and care for students. The results of this research can be used as an example for other schools to pay attention to student health and make healthy lifestyles part of their school culture.Keywords: Strategy, Culture, and Healthy Lifestyle.